Leading through change: A study of the role of central office leadership in the process of secondary change - Halupnik, Dirk A. (2013)
The purpose of this study was to more fully understand the actions of district level leaders in a major change effort and their effects on the change process. Furthermore this study aimed to provide additional information about the factors that school district central office administrators confront when making the decision to add another high school and the actions taken by these administrators to lead the district through this process so that other school districts and leaders may learn from this. The methodology for this study was a qualitative case study approach in which central office leaders in a district that had recently gone through this process were interviewed using a semi-structured interview technique. Five research questions framed this study. 1. What were the antecedents and major factors used to determine the need for a second high school? 2. How did district leaders plan for change? 3. How did district leaders lead the community through change? 4. What impact has this process had on the district leaders? 5. What new challenges has this process brought about? The findings in this study showed that Jackson central office leaders demonstrated significant attention to leading through change. Key change leadership strategies were used effectively by the district level leaders in Jackson as they moved through the transition planning process to a two high school system. Effective communication created a link between the vision for the future of Jackson and the importance of the work. Stakeholders were involved in the planning process at every step. District leaders took responsibility for the plans and they took action. Through this they also remained flexible, adjusting the pace of the work as necessary. Ultimately, a process was put in motion to address change. The areas of relationships, communication, culture, and community involvement were key focus areas in the change process in the Jackson school district. These areas along with continued growth and equity will continue to be areas of concentration for the district leaders. Despite the fact that each of the participants has undergone professional changes, the district leaders demonstrated a remarkable overall positivity concerning the transition process